Development of a Senior Medical Student Robotic Surgery Training Elective. (June 2021) - Mullens, Cody Lendon; Van Horn, Alexandra L; Marsh, James Wallis; Hogg, Melissa E; Thomay, Alan A; Schmidt, Carl R; Boone, Brian A
As robotic surgery has become more widespread, early exposure to the robotic platform is becoming increasingly important, not only to graduate medical education, but also for medical students pursuing surgical residency. In an effort to orient students to robotic technology and decrease the learning curve for what is likely to become an integral part of residency training, we created a formal, elective robotic surgery curriculum for senior medical students. Throughout this 2-week fourth year rotation, students completed online training modules and assessment; mastered exercises on the simulator system related to the console, camera, energy, dexterity, and suturing skills; attended didactics; utilized the dual console during one-on-one simulation lab sessions with attending robotic surgery experts; and translated new skills to biotissue anastomoses as well as bedside-assisting in the operating room. During cases, students were able to have more meaningful observation experiences, recognizing the significance of various robotic approaches employed and utilization of specific instruments. Future aims of this rotation will assess student experience as it impacts readiness for surgical residency.